CATEGORY OF FAIRNESS IN SOCIO-PHILOSOPHICAL INTERPRETATIONS OF THE CONTEMPORARY SYSTEM OF INTERNATIONAL RELATIONS - Kharchenko, S. P. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The phenomenon of "fairness" as the fundamental category in contemporary philosophy, ethics, axiology, philosophy of politics, political ethics, philosophy of law, is conceptualized on the basis of cultural, politico-cultural, linguistic, comparative approaches. Its social philosophical deconstruction in the paradigm of the classical model of international relations is carried out. It is shown that this model provides for the formulation of equitable approaches to enable all the representatives of the international community is equivalent positions to build their own lives, taking into account the cultural traditions, mentality, nuances of national economy and education.